Difficulties and recommendations faced by school mental health education in the information age - Xu, Lingru (Transactions on Social Science, Education and Humanities Research, 2024)
Students’ mental health deserves serious attention. Research shows that school mental health education helps a lot in solving the problem. But with the rise of the information age, education is facing some difficulties that didn’t appear in previous ages. The purpose of this paper is to explore the difficulties faced by school mental health education and the possibility of getting out of the difficulties. This passage raises four problems including the difficulty of tracking students’ mental condition, lack of online treatments and data security, Imprecise information and online dangers, and the relic of old problems. Targeting problems above, three kinds of recommendations which cores specify, digital treatments, and tradition are given. This paper mainly studies the Difficulties faced by school mental health education in the information age and gives some recommendations, including building a progressive system, adding some digital treatments, and mixing the tradition with the new age.